The Rest of the Story: Print News Components in Agricultural Communications Programs at Land·Grant Universities - Edward J. Smith; Ricky W. Telg; Don E. Tomlinson (Journal of Applied Communications, 1994)
The purpose of this study was to learn about print news units within agricultural communications departments across the land-grant university system.